If \[\sin \theta =3\sin \left( \theta +2\alpha \right),\] then the value of \[\tan \left( \theta +\alpha \right)+2\tan \alpha \] is:
A. 3
B. 2
C. 1
D. 0
Answer
Verified
502.8k+ views
Hint: Use the Componendo Dividendo rule in the given expression. Apply trigonometric identities and simplify the expression to get the expression as \[\tan \left( \theta +\alpha \right)+2\tan \alpha \].
Complete step by step solution:
Given is the expression \[\sin \theta =3\sin \left( \theta +2\alpha \right)\]
\[\therefore \dfrac{\sin \theta }{\sin \left( \theta +2\alpha \right)}=3.\]
Let us use the Componendo Dividendo rule to solve the above expression.
Componendo Dividendo is a theorem on proportions which is used to perform calculations and reduce the number of steps.
According to Componendo Dividendo if \[\dfrac{a}{b}=\dfrac{c}{d},\]then it implies that \[\dfrac{a+b}{a-b}=\dfrac{c+d}{c-d}.......(1)\]
Thus applying Componendo Dividendo rule in the expression in equation (1),
\[\dfrac{\sin \theta }{\sin \left( \theta +2\alpha \right)}=\dfrac{3}{1}......(2)\]
Where,
\[\begin{align}
& a=\sin \theta \\
& b=\sin \left( \theta +2\alpha \right) \\
& c=3 \\
& d=1 \\
\end{align}\]
\[\begin{align}
& \therefore \dfrac{a+b}{a-b}=\dfrac{c+d}{c-d} \\
& \Rightarrow \dfrac{\sin \theta +\sin \left( \theta +2\alpha \right)}{\sin \theta -\sin \left( \theta +2\alpha \right)}=\dfrac{3+1}{3-1} \\
& \Rightarrow \dfrac{\sin \theta +\sin \left( \theta +2\alpha \right)}{\sin \theta -\sin \left( \theta +2\alpha \right)}=\dfrac{4}{2}=2......(3) \\
\end{align}\]
We know the trigonometric identities,
\[\begin{align}
& \operatorname{sinx}+siny=2sin\left( \dfrac{x+y}{2} \right)\cos \left( \dfrac{x-y}{2} \right) \\
& \sin x-\sin y=2\cos \left( \dfrac{x+y}{2} \right)\sin \left( \dfrac{x-y}{2} \right) \\
\end{align}\]
Let us apply these identities in equation (3).
\[x=\theta \]and\[y=\left( \theta +2\alpha \right)\].
\[\therefore \dfrac{2\sin \left( \dfrac{\theta +\theta +2\alpha }{2} \right)\cos \left( \dfrac{\theta -\theta -2\alpha }{2} \right)}{2\cos \left( \dfrac{\theta +\theta +2\alpha }{2} \right)\sin \left( \dfrac{\theta -\theta -2\alpha }{2} \right)}=2\]
By simplifying the expression, we get,
\[\begin{align}
& \Rightarrow \dfrac{\sin \left( \dfrac{2\theta +2\alpha }{2} \right)\cos \left( \dfrac{-2\alpha }{2} \right)}{\cos \left( \dfrac{2\theta +2\alpha }{2} \right)\sin \left( \dfrac{-2\alpha }{2} \right)}=2 \\
& \Rightarrow \dfrac{\sin \left( \theta +\alpha \right)\cos \left( -\alpha \right)}{\cos \left( \theta +\alpha \right)\sin \left( -\alpha \right)}=2 \\
\end{align}\]
The cosine is an even function, thus \[\cos (-\alpha )=\cos \alpha\].
The sine is an odd function, so \[sin(-\alpha )=-\sin \alpha \].
\[\dfrac{\sin \left( \theta +\alpha \right)\cos \left( \alpha \right)}{-\cos \left( \theta +\alpha \right)\sin \left( \alpha \right)}=2\]. By cross multiplying, we get,
\[\Rightarrow \dfrac{\sin \left( \theta +\alpha \right)}{\cos \left( \theta +\alpha \right)}=\dfrac{-2\sin \alpha }{\cos \alpha }\].
We know that \[\tan \theta =\dfrac{\sin \theta }{\cos \theta }.\]
\[\begin{align}
& \therefore \tan (\theta +\alpha )=-2\tan \alpha \\
& \Rightarrow \tan (\theta +\alpha )+2\tan \alpha =0 \\
\end{align}\]
Thus we got the value of \[\tan (\theta +\alpha )+2\tan \alpha \] as 0.
Hence option D is the correct answer.
Note:
Remember the basic trigonometric identities like \[(sinA+sinB)\] and \[(sinA-sinB)\] which we have used here. They are very important for solving expressions like these. Just apply the formula and simplify it and you will get the answer.
Complete step by step solution:
Given is the expression \[\sin \theta =3\sin \left( \theta +2\alpha \right)\]
\[\therefore \dfrac{\sin \theta }{\sin \left( \theta +2\alpha \right)}=3.\]
Let us use the Componendo Dividendo rule to solve the above expression.
Componendo Dividendo is a theorem on proportions which is used to perform calculations and reduce the number of steps.
According to Componendo Dividendo if \[\dfrac{a}{b}=\dfrac{c}{d},\]then it implies that \[\dfrac{a+b}{a-b}=\dfrac{c+d}{c-d}.......(1)\]
Thus applying Componendo Dividendo rule in the expression in equation (1),
\[\dfrac{\sin \theta }{\sin \left( \theta +2\alpha \right)}=\dfrac{3}{1}......(2)\]
Where,
\[\begin{align}
& a=\sin \theta \\
& b=\sin \left( \theta +2\alpha \right) \\
& c=3 \\
& d=1 \\
\end{align}\]
\[\begin{align}
& \therefore \dfrac{a+b}{a-b}=\dfrac{c+d}{c-d} \\
& \Rightarrow \dfrac{\sin \theta +\sin \left( \theta +2\alpha \right)}{\sin \theta -\sin \left( \theta +2\alpha \right)}=\dfrac{3+1}{3-1} \\
& \Rightarrow \dfrac{\sin \theta +\sin \left( \theta +2\alpha \right)}{\sin \theta -\sin \left( \theta +2\alpha \right)}=\dfrac{4}{2}=2......(3) \\
\end{align}\]
We know the trigonometric identities,
\[\begin{align}
& \operatorname{sinx}+siny=2sin\left( \dfrac{x+y}{2} \right)\cos \left( \dfrac{x-y}{2} \right) \\
& \sin x-\sin y=2\cos \left( \dfrac{x+y}{2} \right)\sin \left( \dfrac{x-y}{2} \right) \\
\end{align}\]
Let us apply these identities in equation (3).
\[x=\theta \]and\[y=\left( \theta +2\alpha \right)\].
\[\therefore \dfrac{2\sin \left( \dfrac{\theta +\theta +2\alpha }{2} \right)\cos \left( \dfrac{\theta -\theta -2\alpha }{2} \right)}{2\cos \left( \dfrac{\theta +\theta +2\alpha }{2} \right)\sin \left( \dfrac{\theta -\theta -2\alpha }{2} \right)}=2\]
By simplifying the expression, we get,
\[\begin{align}
& \Rightarrow \dfrac{\sin \left( \dfrac{2\theta +2\alpha }{2} \right)\cos \left( \dfrac{-2\alpha }{2} \right)}{\cos \left( \dfrac{2\theta +2\alpha }{2} \right)\sin \left( \dfrac{-2\alpha }{2} \right)}=2 \\
& \Rightarrow \dfrac{\sin \left( \theta +\alpha \right)\cos \left( -\alpha \right)}{\cos \left( \theta +\alpha \right)\sin \left( -\alpha \right)}=2 \\
\end{align}\]
The cosine is an even function, thus \[\cos (-\alpha )=\cos \alpha\].
The sine is an odd function, so \[sin(-\alpha )=-\sin \alpha \].
\[\dfrac{\sin \left( \theta +\alpha \right)\cos \left( \alpha \right)}{-\cos \left( \theta +\alpha \right)\sin \left( \alpha \right)}=2\]. By cross multiplying, we get,
\[\Rightarrow \dfrac{\sin \left( \theta +\alpha \right)}{\cos \left( \theta +\alpha \right)}=\dfrac{-2\sin \alpha }{\cos \alpha }\].
We know that \[\tan \theta =\dfrac{\sin \theta }{\cos \theta }.\]
\[\begin{align}
& \therefore \tan (\theta +\alpha )=-2\tan \alpha \\
& \Rightarrow \tan (\theta +\alpha )+2\tan \alpha =0 \\
\end{align}\]
Thus we got the value of \[\tan (\theta +\alpha )+2\tan \alpha \] as 0.
Hence option D is the correct answer.
Note:
Remember the basic trigonometric identities like \[(sinA+sinB)\] and \[(sinA-sinB)\] which we have used here. They are very important for solving expressions like these. Just apply the formula and simplify it and you will get the answer.
Recently Updated Pages
Master Class 11 English: Engaging Questions & Answers for Success
Master Class 11 Computer Science: Engaging Questions & Answers for Success
Master Class 11 Maths: Engaging Questions & Answers for Success
Master Class 11 Social Science: Engaging Questions & Answers for Success
Master Class 11 Economics: Engaging Questions & Answers for Success
Master Class 11 Business Studies: Engaging Questions & Answers for Success
Trending doubts
10 examples of friction in our daily life
What problem did Carter face when he reached the mummy class 11 english CBSE
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
State and prove Bernoullis theorem class 11 physics CBSE
The sequence of spore production in Puccinia wheat class 11 biology CBSE